Correlation of Uterine Myoma to Menorrhagia - Sharma, Poonam; Rana, Ashma; Bista, Kesang Diki (Nepal Journal of Obstetrics and Gynaecology, 2011)
DOI: http://dx.doi.org/10.3126/njog.v4i2.5033 NJOG 2010 Jan-Feb; 4(2): 12-17